2016
DOI: 10.1111/jmwh.12359
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing Primary Care Facilities for Childbirth: Findings from a Multilevel Analysis of Skilled Birth Attendance Determinants in Afghanistan

Abstract: Assumptions that women who give birth with a skilled attendant do so at the closest health facility may mask the importance of supply-side determinants of skilled birth attendance. More research based on actual utilization patterns, not assumed catchment areas, is needed to truly understand the factors influencing care-seeking decisions in both emergency and nonemergency situations and to adapt strategies to reduce preventable mortality and morbidity in Afghanistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…The higher odds of bypassing might reflect mothers’ and their families’ increased awareness of the need for specialized care that might not be available at their nearest point of OC. Higher level of maternal education was also associated with bypassing in this setting, which is consistent with the findings from a study conducted in Afghanistan (4). Mothers with higher educational levels might have a better socioeconomic status, which allowed them to cover the extra expense associated with bypassing their nearest facility for childbirth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The higher odds of bypassing might reflect mothers’ and their families’ increased awareness of the need for specialized care that might not be available at their nearest point of OC. Higher level of maternal education was also associated with bypassing in this setting, which is consistent with the findings from a study conducted in Afghanistan (4). Mothers with higher educational levels might have a better socioeconomic status, which allowed them to cover the extra expense associated with bypassing their nearest facility for childbirth.…”
Section: Discussionsupporting
confidence: 91%
“…Studies from Nepal (1), Tanzania (2, 3), Afghanistan (4), and Uganda (5) have shown that women often circumvent their nearest obstetric care (OC) facility for childbirth. Reports suggest that bypassing by parturients varies in different settings.…”
Section: Introductionmentioning
confidence: 99%
“…A growing literature, including but also going beyond the database used in this study, points to inequitable usage of health facilities in terms of the SES and urban/rural characteristics of users [23,34,39]. …”
Section: Discussionmentioning
confidence: 99%
“…The need for alternative approaches beyond health facilities to achieve equity in and in fact universal coverage for child health are the following: (i) there is an exponential decline in the utilization of health facilities with increasing distance to the health facility (particularly more than 5 km or 1 hour walk away) [35], and (ii) there is a need for available and affordable public transportation in order to reach health facilities, which is often absent [33,39]. What is lacking from the literature are in–depth assessments of equity of health care utilization in terms of distance from a health facility and the effect of distance from health facilities on health status, taking into account also whether community–based care is available to those further away from those facilities.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] The findings of the studies conducted between 2001 and 2011 that there is a need to improve health facilities, and to increase the number of professionals in both urban and rural areas in order to improve maternal health. [17][18][19][20][21][22][23][24][25][26] Published research suggests that the provision of expanded health services alone would not lead to the increased utilization of Bartlett et al found that 93% of women who died due to maternity-related causes were illiterate. 3 …”
Section: Health Carementioning
confidence: 99%